Exploring the Applicability of Calorespirometry to Assess Seed Metabolic Stability Upon Temperature Stress Conditions—Pisum sativum L. Used as a Case Study - Rodrigues, Lénia; Nogales, Amaia; Hansen, Lee D.; Santos, Fátima; Rato, Ana Elisa; Cardoso, Hélia (Frontiers in Plant Science, 2022)
The availability of phenotyping tools to assist breeding programs in the selection of high-quality crop seeds is of obvious interest with consequences for both seed producers and consumers. Seed germination involves the activation of several metabolic pathways, including cellular respiration to provide the required ATP and reducing power. This work tested the applicability of calorespirometry, the simultaneous measurement of heat and CO2 rates, as a phenotyping tool to assess seed respiratory properties as a function of temperature. The effect of temperature on seed germination was evaluated after 16 h of seed imbibition by calorespirometric experiments run in isothermal mode at 15, 20, 25 and 28°C on seeds of three cultivars of peas (Pisum sativum L.) commonly used in conventional agriculture (cv. ‘Rondo’, ‘Torta de Quebrar’ and ‘Maravilha d’América’). Significant differences in metabolic heat rate and CO2 production rate as well as in the temperature responses of these parameters were found among the three cultivars. A seed germination trial was conducted during six days of imbibition to evaluate the predictive power of the parameters derived from the calorespirometric measurements. The germination trial showed the optimal germination temperature was 20ºC and low germination rates for were observed at extreme temperatures (15°C or 28ºC). The cv. ‘Torta de Quebrar’ showed significantly higher germination in comparison with the other two cultivars at all three temperatures. In comparison with the other two cultivars, ‘Torta de Quebrar’ has the lowest metabolic heat and CO2 rates and the smallest temperature dependence of these measured parameters. Additionally, ‘Torta de Quebrar’ has the lowest values of growth rate and carbon use efficiency calculated from the measured variables.